Evaluating consumers benefits in electronic-commerce using fuzzy TOPSIS - Rakesh Kumar; Janjhyam Venkata Naga Ramesh; Sachi Nandan Mohanty; Muhammad Rafiq; Iskandar Shernazarov; M. Ijaz Khan (Results in Control and Optimization)
Online platforms are preferred by customers when choosing and buying products. The contemporary digital era is witness to e-commerce platforms. Customers rely on various aspects of an e-commerce website for their needs. Sometimes they get more benefit from other digital platforms. This research focusses on how consumers can benefit from digital platforms. The study explores how consumers can embrace a website by leveraging various factors on an online business. The study identified five advantage factors, each offering six benefits, based on previous literature reviews. The study conducted interviews with E-marketing experts based on a questionnaire. This Research used Fuzzy TOPSIS method to determined ranking of most advantageous factor. The factors that provide advantages include usability, service quality, information quality, and online trust. The research analyses the ranking of these factors based on results. The research finds that usability of a website, i.e., functionality, efficiency, and search mechanism, is the most important advantage factor. This research is useful for businesspeople who engage in e-commerce platforms. The study explores future scope of research like cost, time, and regional issues on different products and regions.